Benefits Of Productive Zakat In Increasing Mustahik Revenue In Lazismu Center - Syahrul Amsari; Salman Nasution (Proceeding International Seminar of Islamic Studies, 2019)
This study aims to find out how the benefits of productive zakat applied in LAZISMu are then also the model applied in the empowerment of mustahik so that it is known whether the income mustahik after getting productive zakat funds from LAZISMu there is an increase or change in terms of income, business ethics and the ability to pay ZIS . LAZISMu in making productive zakat through economic programs that aim to create entrepreneurs and provide new jobs for people who do not have jobs. The research method used is a qualitative method that is to analyze and describe the results of the data obtained with the form of words. The results showed that from the indicators of mustahik empowerment, the impact of the mustahik empowerment of the Amanah Family Economic Development program, from these results it can be drawn that ZIS has been beneficial in empowering mustahik. In the utilization of productive zakat, LAZISMu, aside from its distribution, is carried out on its own, it also always optimizes the Assembly, Institutions and Orthom in the Muhammadiyah environment to have a wider impact on the beneficiaries and the program is more varied.